Profile Quantitative Hepatitis B Surface Antigen (qHBsAg) of Chronic Nai?ve Hepatitis B Patients in Dr. Soetomo Hospital, Surabaya, Indonesia - Yessy Puspitasari; Puspa Wardhani; Munawaroh Fitriyah; Erik Hasudungan; Atika; Ummi Maimunah; Aryati (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aimed to evaluate the profile of qHBs Ag profile, and also to investigate the correlation betweenqHBs Ag and HBV DNA. Seventy samples of chronic-nai?ve hepatitis B patients in Dr. Soetomo Hospitalwere analyzed in a cross-sectional study. Patients were categorized according to the HBe Ag positive (n=30)and HBe Ag negative (n=18), also based on qHBs Ag 1000 IU/mL and qHBs Ag >1000 IU/mL. qHBs Agwas correlated with HBV DNA. qHBs Ag by CLEIA method from Sysmex, KOBE HISCL, HBV DNAwas measured by real-time Polymerase Chain method from Gene Xpert, Cepheid. 70 patients nai?ve CHBtreatment showed a median of ALT level 60.21±70.76 U/L. 30 patients showed a positive-HBeAg, 18 patientsshowed negative-HBeAg, 22 patients were not evaluated (N/A). Positive-HBeAg patients had 70% qHBsAg>2500 mg/dL and median HBV DNA 7.49×107IU/mL. Negative-HBeAg patients had 55.6% HBsAg ?1000mg/dL and median HBV DNA 9.66×102 IU/mL. qHBsAg correlated with HBV DNA (p <0.001). This datademonstrated that quantitative HBsAg was associated with a phase of HBV-infection, quantitative HBsAgshowed a moderate correlation with DNA HBV, quantitative HBsAg levels might be a predictor of initiationtherapy for CHB patients.